2021
DOI: 10.1016/j.molstruc.2021.130076
|View full text |Cite
|
Sign up to set email alerts
|

Computational search for drug repurposing to identify potential inhibitors against SARS-COV-2 using Molecular Docking, QTAIM and IQA methods in viral Spike protein – Human ACE2 interface

Abstract: With the advancement of the Covid-19 pandemic, this work aims to find molecules that can inhibit the attraction between the Spike proteins of the SARS-COV-2 virus and human ACE2. The results of molecular docking positioned four molecules at the interaction site Tyr-491(Spike)-Glu-37(ACE2) and one at the site Gly-488(Spike)-Lys-353(ACE2). The QTAIM and IQA data showed that the 1629 molecule had a significant inhibitory effect on the Gly488-Ly353 site, decreasing the Laplacian of the electronic density of the BC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
3
0
1
Order By: Relevance
“…Yadav et al suggested the higher reactivity of favipiravir toward Mpro since the presence of electron donor and receptor groups in favipiravir displayed the capability of forming a complex with the external target molecule. Other similar studies include refs and . DFT calculations by Aitouna et al , indicated the epoxidation reaction of parthenolide and himachalene derivatives presented high chemoselectivity.…”
Section: Methods and Approachesmentioning
confidence: 83%
“…Yadav et al suggested the higher reactivity of favipiravir toward Mpro since the presence of electron donor and receptor groups in favipiravir displayed the capability of forming a complex with the external target molecule. Other similar studies include refs and . DFT calculations by Aitouna et al , indicated the epoxidation reaction of parthenolide and himachalene derivatives presented high chemoselectivity.…”
Section: Methods and Approachesmentioning
confidence: 83%
“…Dipyridamole, candesartan cilexetil, candesartan, oxytetracycline, valganciclovir hydrochloride, roxatidine acetate, omeprazole, sulfacetamide, cimetidine, disulfiram, atazanavir, hydroxychloroquine, chloroquine, indinavir montelukast sodium, and maribavir [83] Membrane (M) protein 3I6G Colchicine, remdesivir, bafilomycin A1, temozolomide, and colchicine derivatives [84] Nucleocapsid (N) protein 6M3M Apamycin, camostat, nafamostat, saracatinib, trametinib, cefuroxime, ceftriaxone, cefotaxime [85] RNA-dependent RNA polymerase (RdRp) 7D4F molnupiravir, grazoprevir, ganciclovir, atazanavir, daclatasvir, acyclovir, etravirine, entecavir, efavirenz, asunaprevir, abacavir dolutegravir, lomibuvir, penciclovir, trifluridine, danoprevir, ritonavir, saquinavir, raltegravir, and lamivudine [86] S-protein 6VXX Pemirolast, isoniazid pyruvate, nitrofurantoin, and eriodictyol [87]…”
Section: Targets Pdb Id Repurposed Drugs Referencesmentioning
confidence: 99%
“…According to the pathogenesis of SARS-CoV-2 from the perspective of S protein and ACE2 binding, they found some substances, including peptide P6, griffithsin, EK1 and extracts from traditional chinese medicine, which fought against SARS-CoV-2 through binding ACE2 receptor, S protein, or inhibiting the host and virus. Faria et al [ 132 ] also focused on the molecules that can inhibit the interaction between the S protein and human ACE2. They discovered some molecules at the interaction sites: four molecules in Tyr-491(Spike)-Glu-37(ACE2) and one in Gly-488(Spike)-Lys-353(ACE2).…”
Section: Cadd Against Sars-cov-2: Targeting the Structure Proteinmentioning
confidence: 99%